Method to Locate a Shelf and Slot with Ordered Items: Decision of the Supreme People’s Court of China 8 April 2021 – Case No. (2020) Zui Gao Fa Zhi Min Zhong No. 1469 (IIC - International Review of Intellectual Property and Competition Law, 2024)
The title as an integral part of a preamble has a limiting effect on the scope of protection of an independent claim. Under normal circumstances, when determining the scope of protection of a claim, all technical features pertaining to a claim must be considered, and the exact limiting effect of each technical feature is ultimately reflected in the subject-matter protected by the claim. The subject-matter of a claim can be a method, a product, an apparatus or a material, and it could also be the application or method of application of these subject-matters. When making an independent claim, the filing document is required to comprise two parts: a preamble and a technical features section. The purpose of this requirement is to enable the public to clearly identify which technical features of an independent claim are known in the closest prior art and which are novel over the closest prior art. Therefore, a complete technical solution, which consists of a preamble and a technical features section, is protected by the patent rights. A technical solution disclosed in a title needs to be supported by all of the technical features in the claim. Therefore, a title is a high-level summary of a technical solution, which includes every technical feature described in the claim, and it is also a simple designation of a technical solution. The title and the technical features are not one and the same. Rather, they are equal parts of a claim. The title of a claim is considered to have a limiting effect on the scope of protection of a technical solution. However, the limiting effect of a title must be viewed as a general limitation on a technical solution, which is different from the micro-limitation imposed on a technical solution by specific technical features of a claim. A term that is repeatedly used in the same document shall have the same interpretation, and different terms shall have different interpretations. According to the Doctrine of Equivalents, elements used for comparisons are technical features of a claimed patent and its variants, instead of technical solutions as a whole.